Upaya Meningkatkan Hasil Belajar IPA Menggunakan Model Pembelajaran Project-Based Learning pada Siswa Kelas V Di SDN-11 Palangka - Wila; Rumiati; Tribuani (Jurnal Pendidikan Dasar dan Menengah, 2024)
This study used the Classroom Action Research method which was carried out in two cycles with the aim of determining the effectiveness of using a project-based learning model in improving the learning outcomes of science subject in the fifth-grade students of SDN-11 Palangka, Kota Palangka Raya. This study was based on observation and interview with a classroom teacher at the school where researchers found problem in student learning outcomes. One of problems is that there were still many students who have not mastered the learning material of the science subject because the average score achieved was 70.4 where this score is still below the Minimum Completeness Criteria (KKM) standardized by the school, which is 75. To solve the problem, researchers tried to use the project-based learning model as a solution. The results showed that the teacher's activity score increased from cycle I to cycle II with the achievement criteria from the category of "good" to "very good". In addition, student activities from cycle I to cycle II also increased with the achievement criteria from the category of "fairly good" to "very good". Regarding the completeness of student learning outcomes in the first cycle, it showed 65% of students reached the KKM and it increased in the second cycle to 92%. Based on the data, it can be concluded that the use of project-based learning model can improve the learning outcomes of students in the science subject of the fifth graders.